Dynamics in perioperative neutrophil-to-lymphocyte*platelet ratio as a predictor of early acute kidney injury following cardiovascular surgery. Issue 1 (1st January 2021) - Li, Yang; Zou, Zhouping; Zhang, Yunlu; Zhu, Bowen; Ning, Yichun; Shen, Bo; Wang, Chunsheng; Luo, Zhe; Xu, Jiarui; Ding, Xiaoqiang
Abstract: Background: In this study, we applied a composite index of neutrophil-lymphocyte * platelet ratio (NLPR), and explore the significance of the dynamics of perioperative NLPR in predicting cardiac surgery-associated acute kidney injury (CSA-AKI). Methods: During July 1 st and December 31 th 2019, participants were prospectively derived from the 'Zhongshan Cardiovascular Surgery Cohort'. NLPR was determined using neutrophil counts, lymphocyte and platelet count at the two-time points. Dose-response relationship analyses were applied to delineate the non-linear odds ratio (OR) of CSA-AKI in different NLPR levels. Then NLPRs were integrated into the generalized estimating equation (GEE) to predict the risk of AKI. Results: Of 2449 patients receiving cardiovascular surgery, 838 (34.2%) cases developed CSA-AKI with stage 1 ( n  = 658, 26.9%), stage 2–3 ( n  = 180, 7.3%). Compared with non-AKI patients, both preoperative and postoperative NLPR were higher in AKI patients (1.1[0.8, 1.8] vs. 0.9[0.7, 1.4], p  < 0.001; 12.4[7.5, 20.0] vs. 10.1[6.4, 16.7], p  < 0.001). Such an effect was a 'J'-shaped relationship: CSA-AKI's risk was relatively flat until 1.0 of preoperative NLPR and increased rapidly afterward, with an odds ratio of 1.13 (1.06–1.19) per 1 unit. Similarly, patients whose postoperative NLPR value >11.0 were more likely to develop AKI with an OR of 1.02. Integrating the dynamic NLPRs into the GEE model, we found that the AUC was 0.806(95% CI 0.793–0.819), which was significantly higher than the AUC without NLPR (0.799, p  < 0.001). Conclusion: Dynamics of perioperative NPLR is a promising marker for predicting acute kidney injury. It will facilitate AKI risk management and allow clinicians to intervene early so as to reverse renal damage.